Parenting and pandemic pressures: Examining nuances in parent, child, and family well-being concerns during COVID-19 in a Canadian sample - Colucci, Laura; Smith, Jackson A.; Browne, Dillon T. (Frontiers in Epidemiology, 2023)
The COVID-19 pandemic has caused vast disruptions in family life for Canadian parents since early 2020. While numerous environmental stressors have been identified, including job loss and the demands of balancing work-life conflicts and at-home schooling, relatively less is known about the areas of family life parents are most concerned about and how these worries relate to well-being across the family system. Canadian parents (n=29831, 90.29% mothers, 57.40% Ontario residents) of children aged 0-14 were surveyed about their concerns related to child, parent, and family well-being in June 2020. Structural equation modelling was used to model the relationship between concerns about children, parenting, and the whole family, in association with several sociodemographic variables including child disability status, parent sex and education, job loss during COVID-19, and caregiver employment. Parenting, child, and family concerns were positively correlated. Higher child and family concerns were reported by parents who had not attended university, those who had experienced employment loss or reduced hours, and families with all adults working outside the home. Parents of children with a disability reported higher concerns across all three domains: child, parenting, and family psychosocial well-being. These results showcase distinct associations between social determinants of health and the types of worries caregivers exhibited across multiple areas of family life during the first wave of the COVID-19 pandemic in Canada. Findings are interpreted in relation to clinical intervention and public policy targets for families.